2011
DOI: 10.1016/j.ajpath.2011.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation Triggers Metalloproteinases Release Inducing Cervical Remodeling and Preterm Birth in Mice

Abstract: Inflammation is frequently linked to preterm delivery (PTD). Here, we tested the hypothesis that complement activation plays a role in cervical remodeling and PTD. We studied two mouse models of inflammation-induced PTD. The first model was induced by vaginal administration of lipopolysaccharide (LPS) and the second one by administration of progesterone antagonist RU486. Increased cervical C3 deposition and macrophages infiltration and increased serum C3adesArg and C5adesArg levels were observed in both models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
179
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(192 citation statements)
references
References 44 publications
8
179
3
2
Order By: Relevance
“…Similar signaling cascades may be activated by noninfectious inflammation, triggered by damage-associated molecular patterns (DAMPs), which activate signals such as the receptor for advanced glycation end products (RAGE) and resulting in the production of parturition-triggering cytokines (49). Inflammatory mediators also activate complement, which contributes to cervical remodeling and PTB (50). These diverse pathways converge on a set of well-established labor-inducing inflammatory mediators, such as prostaglandins.…”
Section: Established Pathways Implicated In Term and Preterm Parturitionmentioning
confidence: 99%
“…Similar signaling cascades may be activated by noninfectious inflammation, triggered by damage-associated molecular patterns (DAMPs), which activate signals such as the receptor for advanced glycation end products (RAGE) and resulting in the production of parturition-triggering cytokines (49). Inflammatory mediators also activate complement, which contributes to cervical remodeling and PTB (50). These diverse pathways converge on a set of well-established labor-inducing inflammatory mediators, such as prostaglandins.…”
Section: Established Pathways Implicated In Term and Preterm Parturitionmentioning
confidence: 99%
“…membranes, lead to a decreased tensile strength ofthe chorioamniotic membrane, suggesting a correlation between increased levels of these molecules and the risk of PPROM and PTD (10)(11)(12). The detection of intrauterine inflammation as early PTD risk factor is based not only on the search of relevant AF markers, but also on the choice of the most appropriate diagnostic tool.…”
mentioning
confidence: 99%
“…83 Depletion of macrophages prevented cervical remodeling and preterm delivery in lipopolysaccharide-treated mice. 84 Our study of macrophage phenotypes showed that during preterm labor induced by double hit of PGN1poly(I : C), increased the number of macrophages (F4/ 801) that were double-positive for CD11c and CD206. 26 Wentworth et al 85 has demonstrated these double positive CD11c…”
Section: Preterm Labor and Macrophage Phenotypesmentioning
confidence: 99%